Algebra-Finanzmathematik-Zinseszinsformel


  • $K_{t} = K_{0} \cdot (1 + \frac{ p}{100})^{t}$
    1 2 3 4 5 6
    $K_{0} = \frac{ K_{t} }{(1 + \frac{ p}{100})^{t} }$
    1 2 3 4 5 6
    $p = (^{t} \sqrt{\frac{K_{t} }{K_{0} }}-1)\cdot 100$
    1 2 3 4 5 6
    $t =\frac{\ln(K_{t} ) - \ln(K_{0} )}{\ln(1 + \frac{ p}{100})}$
    1 2 3 4 5 6

Beispiel Nr: 03
$\text{Gegeben:}\\\text{Anzahl der Jahre} \qquad t \qquad \\ \text{Zinssatz} \qquad p \qquad [\%] \\ \text{Kapital nach t Jahren} \qquad K_{t} \qquad [Euro] \\ \\ \text{Gesucht:} \\\text{Anfangskapital} \qquad K_{0} \qquad [Euro] \\ \\ K_{0} = \frac{ K_{t} }{(1 + \frac{ p}{100})^{t} }\\ \textbf{Gegeben:} \\ t=1 \qquad p=7\% \qquad K_{t}=9Euro \qquad \\ \\ \textbf{Rechnung:} \\K_{0} = \frac{ K_{t} }{(1 + \frac{ p}{100})^{t} } \\ t=1\\ p=7\%\\ K_{t}=9Euro\\ K_{0} = \frac{ 9Euro }{(1 + \frac{ 7\%}{100})^{1} }\\\\ K_{0}=8\frac{44}{107}Euro \\\\$